2016
DOI: 10.1007/978-3-662-53174-7_23
|View full text |Cite
|
Sign up to set email alerts
|

Colouring and Covering Nowhere Dense Graphs

Abstract: In [12] it was shown that nowhere dense classes of graphs admit sparse neighbourhood covers of small degree. We show that a monotone graph class admits sparse neighbourhood covers if and only if it is nowhere dense. The existence of such covers for nowhere dense classes is established through bounds on so-called weak colouring numbers. The core results of this paper are various lower and upper bounds on the weak colouring numbers and other, closely related generalised colouring numbers. We prove tight bounds f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 22 publications
0
46
0
Order By: Relevance
“…More explicitly, for every graph G we have the following relations. The equality col ∞ (G) = tw(G) + 1 was first proved in [10]; for completeness we include the proof in Subsection 2.2. The equality wcol ∞ (G) = td(G) is proved in [22,Lemma 6.5].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…More explicitly, for every graph G we have the following relations. The equality col ∞ (G) = tw(G) + 1 was first proved in [10]; for completeness we include the proof in Subsection 2.2. The equality wcol ∞ (G) = td(G) is proved in [22,Lemma 6.5].…”
Section: Introductionmentioning
confidence: 95%
“…• Lower bounds for the generalised colouring numbers for minor closed classes are given in [10]. In that paper it is shown that for every k and every r there is a graph G k,r of treewidth k that satisfies col r (G k,r ) = k + 1 and wcol r (G k,r ) = r+k k .…”
Section: Theorem 15mentioning
confidence: 99%
See 2 more Smart Citations
“…We next show that if the considered tree decomposition has small adhesion, then every vertex reaches only a small number of vertices via short paths in the skeleton. The argument essentially boils down to the combinatorial core of the proof that graphs of treewidth k have weak p-coloring number O(p k ) [20]. Lemma 24.…”
mentioning
confidence: 99%